2024
DOI: 10.32942/x23g71
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The rarity of Invertebrates prevents reliable application of IUCN Red-List criteria.

Robert Goodsell,
Ayco Tack,
Fredrik Ronquist
et al.

Abstract: Among the most widely used information underpinning international conservation efforts is the IUCN Red List of endangered species. The Red List designates species extinction risk based on geographic range, population size, or declines in either. However, the Red-List has poor representation of invertebrates which comprise the majority of animal diversity, and it has frequently been questioned whether Red List criteria are appropriate for these organisms. Due to their small size, difficulty in identification, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Thus, potential candidates, such as Strongylognathus bulgaricus , S. huberi dalmaticus and Teleutomyrmex buschingeri , should be listed, as are their congeners. However, estimation of population sizes and ranges for these and many other invertebrates implies the introduction of potential new IUCN criteria to reflect more accurately their conservation needs ( Goodsell et al 2024 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, potential candidates, such as Strongylognathus bulgaricus , S. huberi dalmaticus and Teleutomyrmex buschingeri , should be listed, as are their congeners. However, estimation of population sizes and ranges for these and many other invertebrates implies the introduction of potential new IUCN criteria to reflect more accurately their conservation needs ( Goodsell et al 2024 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, most biodiversity studies cover only a few well-studied groups that are relatively easily identified and quantified (e.g., birds, mammals, amphibians, bees, and butterflies). Such charismatic taxa are then used as proxies for all taxa in a region (Ricklefs 2006; Wiens 2007; Svenning et al 2008; Ollerton 2017; Garda et al 2018; Bell et al 2019; Bogoni et al 2020; Orr et al 2020) instead of basing our understanding of global biodiversity on a broad and unbiased representation of biodiversity covering a wide range of traits and responses to environmental change (Bar-On et al 2018, Goodsell et al 2024).…”
Section: Introductionmentioning
confidence: 99%
“…For some of these species, particularly those at high risk of extinction, whole genome sequences have been determined, and conservation genetic studies have accumulated ( Nakahama et al, 2022 ). Introducing Red lists has aroused controversies about its biased species selection towards organisms with relatively large sizes or those with frequent human experience ( Possingham et al, 2002 ; Cazalis et al, 2022 ; Régnier et al, 2009 ; Goodsell et al, 2024 ), but they serve as one official proxy out of limited existing resources. To facilitate conservation research on endangered species using genome sequences, it is crucial to monitor the current status and tendency of whole genome sequencing for different taxa to prioritize future policies.…”
Section: Introductionmentioning
confidence: 99%